Tingkat adiksi game online pada remaja di SMAN 1 Kasihan Bantul - M. Rizki Farhan; Retno Sumiyarini; Khristina Dias Utami (MEDIA ILMU KESEHATAN, 2023)
Background: Internet users have reached 4.5 billion worldwide. This number indicates that 60% or more than half of the earth’s population has been using the Internet. Objective: To identify the level of online game addiction among teenagers at SMAN 1 Kasihan Bantul. Methods: Used a descriptive quantitative research design of a cross-sectional approach. The population of this research was teenagers in the X class in a total of 286 recruited through stratified random sampling technique which was resulting in 100 samples. Results: From the research result, it was evident that most of the addiction levels among the teenagers at SMAN 1 Kasihan fell into the light category (<55%) in a total of 76 respondents (76%). Conclusion: It was shown that the teenagers at SMAN 1 Kasihan Bantul experience a light online game addiction.